Konstruksi Isu Aktual Bidang Ketahanan Nasional Untuk Pengembangan Isi Pendidikan Kewarganegaraan Persekolahan - Sri Haryati (Jurnal Ketahanan Nasional, 2018)
ABSTRACTThisi study was aimed at to constructed the actual issues of national resilience ini thei developmenti of educational content of civici educationi as a description of knowledge about the actual issue of citizenship in the national resilience studies asi thei content of civici educationi in school.The research used qualitative descriptive approach. Source of informant data with purposive sampling technique, relevant document and literature study. Data collection was done throughi in-depthi interviewsi, FGD, iobservation, and documenti studyi. The validity of data was done by triangulation process of source and method. iData analysisi was done byireduction, data ipresentation, and iconclusion.Thei resultsi showedi thati the description of the content of civic education was based on the actual issues of national resilience concerning ideological, political, economic, socio-cultural and security issues in the form of basic competence study which translated into indicators to achieved the objectives of basic competence. Based on idataianalysis, it wasiinecessary to studiedi theiactual issue of national resilience to supported the content of civic education education in schoolABSTRAKPenelitian ini bertujuan untuk mengkonstruksi isu aktual bidang ketahanan nasional dalam pengembangan isi pendidikan kewarganegaraan persekolahan berupa deskripsi pengetahuan tentang isu aktual kewarganegaraan bidang ketahanan nasional sebagai isi pendidikan kewarganegaraan persekolahan.Penelitian menggunakan pendekatan deskriptif kualitatif. Sumber data informan dengan teknik purposive sampling, dokumen dan kepustakaan yang relevan. Data dikumpulkan dan diolah dengan cara wawancara mendalam, FGD, observasi, dan studi dokumen. Validitas data dilakukan melalui proses trianggulasi sumber dan metode. Data dianalisis melalui reduksi data, pemyajian data, dan penarikan kesimpulan.Penelitian ini menemukan rumusan tentang deskripsi isi pendidikan kewarganegaraan berdasarkan isu aktual bidang ketahanan nasional yaitu tentang isu-isu ipoleksosbudhankam berupa kajian kompetensi dasar yang diterjemahkan menjadi indikator-indikator untuk mencapai tujuan dari kompetensi dasar tersebut. Berdasarkan analisis data, diperlukan kajian isu aktual ketahanan nasional untuk mendukung isi pendidikan kewarganegaraan persekolahan